The Malaysian experience in privatised projects - Kooi, Khuat Chye. (2009)
This paper describes the Malaysian experience in privatised projects. It outlines the Malaysian government's rationale in introducing the privatisation policy in 1983, which is seen as a significant policy departure from the interventionist and centralist policies of the 1970s. The main objectives to be met from the privatisation policy stemmed from the government's decision to recede from staggering involvement in public enterprises. These entities have suffered heavy financial losses as a result of poor efficiency and low productivity in bureaucratic-laden environments.